The Wafaq Manuscript of Lampung: A Textual Study on Esoteric Knowledge and the Islamization of Local Culture - Zikrillah, Zikrillah; Farhani, Aufa Nadiya; Agustina, Nevy; Achmad, Achmad; Erlina, Erlina (JURNAL AT-TURAS, 2026)
This study addresses a significant lacuna in Nusantara Islamic manuscript scholarship, which has predominantly emphasized cataloguing, textual transmission, and codicological description, while leaving the functional, symbolic, and theological dimensions of wafaq practices underexamined. Focusing on a circular wafaq (wafaq dā’irah) manuscript from Lampung containing Q. 48:29 and Q. 2:246, this research investigates how Qur’anic text, geometric symbolism, and local religiosity intersect within the tradition of ʿIlm al-Hikmah. Employing a qualitative-descriptive design that integrates philological, codicological, and hermeneutical approaches, the study analyzes the manuscript’s textual integrity, visual structure, and socio-historical context in the late nineteenth to early twentieth century. The findings demonstrate that the Qur’anic verses were transmitted faithfully according to the ʿUthmānic rasm, yet functionally transformed through circular geometric inscription, shifting from recitative devotion (tilāwah) to visual-symbolic mediation (hirz/azīmah). Genealogically, the manuscript reflects adaptation of classical Middle Eastern esoteric works—particularly Shams al-Maʿārif al-Kubrā and Khazīnat al-Asrār—into a localized Lampung context, evidenced by Pegon annotations and pragmatic spiritual aims such as protection and authority. Beyond documenting syncretization, this study argues that wafaq manuscripts constitute a contested epistemological arena in which orthodoxy, esotericism, and local authority are negotiated. Consequently, Islamization in Lampung is better understood not as linear doctrinal purification but as a process of symbolic internalization and material articulation of sacred text. By foregrounding the theological contestation and socio-symbolic function of wafaq, this research reframes Indonesian Islamic esotericism as an integral, though debated, component of Islamic intellectual history rather than a peripheral magical residue.